CHARACTERIZATION OF VOLATILE ORGANIC COMPOUNDS AND ODOUR POLLUTION IN ATMOSPHERE AT OIL AND GASOLINE HANDLING AND PROCESSING IMPACT ZONE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Air quality pollution problem is still one of the crucial points for citizens in Europe for already receiving increasing attention, particularly because of the major European cities 10 and more years. Although the EU's long-term goal is to achieve levels of air quality that do not impact and risks to human health and the environment, many of member states still didn`t reach stated goals. Additionally, to gaseous pollutants, recently specific type of pollution, - odour, seems to become more important. Usually in order to determine pollution levels, national, municipal and private monitoring equipment is used. For this research municipal monitoring site in Riga (Latvia), at Milgravja Street 10, controlling gaseous pollutants (SO2, O3, BTX, PM10) and airborne particulate matter, and private monitoring results from Riga, Milgravja Street 16, where odour pollution was obtained, are analysed. Distance between both stations are just 500 m. Measurements at municipal monitoring site is obtained by DOAS and gravimetric sampling, while at Milgravja 16 by photoionization method or so-called “electronic nose”. Monitoring results in municipal station show that in 2017 the average benzene concentration was 4,87 ug/m3, toluene – 8,89 ug /m3 and xylene – 5,07 ug/m3, while the odour pollution level does not exceed 5 odour units. In general estimation of pollution averaged annually do not show and explain variability of pollution levels. It`s well known that high BTX and odour pollution episodes occur in shorter periods, thus short term limit values would be useful in order to characterize short term effects on human health and well-being.